Sorption of Heavy Metal Ions from Water by Natural Apatite Ore - Amerkhanova, Sh.K.; Uali, A.S.; Shlyapov, R.M. (Allerton Press, 2018)
The article shows the efficient use of natural apatite ore in purification of mining industrial wastewaters from heavy metal ions. The determination of adsorption constants, calculation of thermodynamic parameters at various pH of the medium were carried out. It was established that the sorbent based on apatite ore may be used in ecological and technological aims in water conditioning and water treatment.
Keywords: apatite ore; adsorption isotherms; Fe3+; Co2+; Ni2+ ions; sorption concentration